The justification of the loser-pays principle in civil litigation - DOUKA, Anastasia (Revista Jurídica Portucalense, 2025)
In civil procedure, there are two main cost allocation rules: the English Rule and the American Rule. The English Rule, also known as the loser-pays principle, stipulates that the losing party must pay all legal expenses. The American Rule states that each party must pay their own attorney fees, regardless of the outcome of the proceedings. This paper critically reviews the primary theories supporting the loser-pays principle in civil litigation, including the theories of strict liability, compensation, procedural risk and policy, and the theory of the initiation of unnecessary costs. According to the teleological approach, which focuses on how litigation costs restrict the right to access to justice, the theory of initiation of unnecessary costs provides the most appropriate foundation for the loser-pays principle. This theory stems from the principle of economy of proceedings, which specifies effective legal protection by identifying the losing party as the party that caused unnecessary litigation costs, which are then logically imposed on that party.